Pengaruh Rasio Profitabilitas Dan Likuiditas Terhadap Financial Distress Pada Perusahaan Otomotif Tahun 2019-2022 - Maryamah, Isnani; Suparno, Suparno (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2023)
Automotive companies are a very important sector for investment and have a significant role in national economic growth. However, an unstable situation such as the Russia-Ukraine war has the potential to hamper economic recovery, both in Indonesia and the world, from the impact of the Covid-19 pandemic. This research was conducted to find out whether profitability and liquidity ratios have an effect on predicting financial distress in automotive companies listed on the IDX in 2019-2022 using the multiple linear regression analysis method. The results of this study are that the profitability ratios have an effect on financial distress while the liquidity ratio has no effect on financial distress. But the ratio of profitability and liquidity together affect financial distress.